1974
DOI: 10.1159/000122246
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Serum LH during the Proestrous Critical Period in Rats Exhibiting Four- or Five-Day Estrous Cycles

Abstract: Many studies have suggested that rats exhibiting 4-dayestrous cycles may differ from those exhibiting 5-day estrous cycles in hormonal secretion rates. The present study was carried out to delineate the pattern of the ovulatory surge of LH secreted in these two types of cycles. During the day of proestrus, 1–3 serum samples per rat were collected by cardiac puncture, under ether anesthesia, at 30-min intervals, from 13.30 to 20.30 h. Serum LH was determined using the 0:0 RIA. No rat had values above 10 ng/ml b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

1975
1975
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 2 publications
(4 reference statements)
1
9
1
Order By: Relevance
“…The sequence of changes in pituitary content and release of LH and FSH of incubated pituitary glands from 4-day cycle rats observed in this study is in agreement with previously published in vivo observations [8,18,30]. Significantly higher LH concentrations in the medium were observed from incubated pituitaries of rats killed on the day of proestrus, with the maximum levels reached in the afternoon.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The sequence of changes in pituitary content and release of LH and FSH of incubated pituitary glands from 4-day cycle rats observed in this study is in agreement with previously published in vivo observations [8,18,30]. Significantly higher LH concentrations in the medium were observed from incubated pituitaries of rats killed on the day of proestrus, with the maximum levels reached in the afternoon.…”
Section: Discussionsupporting
confidence: 92%
“…Fluctuations in pituitary and plasma luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in rats have been studied in detail dur ing the normal 4-and 5-day estrous cycle [7,8,11,18,29,30] and after the administration of gonadotrophin-releasing hormone (GnRH) [2, 20. 23, 39], Contrasting with these numerous publications on in vivo studies, the estrous cycle in vitro has received less attention [9,16,38], It has been established that in vitro procedures provide an excellent system for studying important aspects of the secretory process and the mechanisms of hypothalamic and gonadal hormone action at the pituitary level.…”
Section: Introductionmentioning
confidence: 99%
“…From these experiments, however, it could be not determined whether this difference was caused by differences in hypothalamic LH releasing hormone (LH-RH) secretion, or by differences in pituitary response to the releasing hormone. Nequin, Talley, Mann & Schwartz (1974) found no difference between the preovulatory LH surges of 4d-rats and 5d-rats, though in other experiments Nequin & Schwartz (1971) noted a difference in the timing of mating behaviour in the two groups, a difference which might be caused by different patterns in sex hormone secretion (Schwartz, 1969). On the other hand, Smith, Bowers & Davidson (1973) observed that the pro-oestrous LH surges of 5d-rats are higher than those of 4d-rats.…”
Section: Introductionmentioning
confidence: 87%
“…Data collected in this laboratory over a period of 14 months from 56 control proestrous rats indicated that LH values before the preovulatory surge were usually less than 100 ng/ml whole blood and always less than 200 ng/ml; during the onset of the surge (between 1400 and 1800 h on the afternoon of proestrus (16)(17)(18)), values reach more than 1000 ng/ml. Accordingly, hourly blood samples were drawn from 1200 or 1300 to 1800 h. During initial studies and at various times throughout those reported here, LH values were obtained before, during, and after the preovulatory surge of LH by collecting both 100 fjd plasma plus 10 and 50 fi\ whole blood at each time point.…”
Section: Methodsmentioning
confidence: 96%